2016
DOI: 10.33549/physiolres.933294
|View full text |Cite
|
Sign up to set email alerts
|

Novel Porcine Model of Acute Severe Cardiogenic Shock Developed by Upper-Body Hypoxia

Abstract: Despite the urgent need for experimental research in the field of acute heart failure and, particularly cardiogenic shock, currently there are only limited options in large animal models enabling research using devices applied to human subjects. The majority of available models are either associated with an unacceptably high rate of acute mortality or are incapable of developing sufficient severity of acute heart failure. The objective of our research was to develop a novel large animal model of acute severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…A recent study by our group described hemodynamic effects of VA ECMO on an innovative animal model of acute HF induced by hypoxic coronary perfusion [8,20], and these findings were later confirmed by computer modeling [9]. Similar to our current design, the effects of increasing EBF on LV were reported.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A recent study by our group described hemodynamic effects of VA ECMO on an innovative animal model of acute HF induced by hypoxic coronary perfusion [8,20], and these findings were later confirmed by computer modeling [9]. Similar to our current design, the effects of increasing EBF on LV were reported.…”
Section: Discussionsupporting
confidence: 80%
“…Especially in this context of LV overload, evaluation of VA ECMO in experiments with heart failure (HF) models have become important before translations to clinical practice. LV performance has been studied on models with intact or acutely decompensated hearts [6,8,[19][20][21][22], but to our knowledge, there have been no experimental studies on hemodynamic effects of VA ECMO in conditions of chronic HF and its decompensation. Even though a significant part of VA ECMO clinical applications is for circulatory decompensation developed on grounds of previously present chronic heart disease, we still lack evidence from corresponding experiments.…”
mentioning
confidence: 99%
“…Sixteen female swine ( Sus scrofa domestica , Large White × Landrace crossbreed), four to five months of age and a mean body weight of 45 kg were used. Full details of the animal model used in the present study can be found in previous publications [ 13 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…An initial rapid IV infusion of 1000 mL normal saline was administered after anesthesia induction, followed by a continuous IV drip at a rate of 100 mL/h to 500 mL/h to reach and maintain a mean right atrial pressure of 5 mmHg to 7 mmHg. An unfractionated heparin IV bolus (100 U/kg) was administered after sheath placement, followed by a continuous IV infusion of 50 U/kg/h to maintain an activated clotting time of 200 s to 250 s. Values were monitored every hour using the Hemochron Jr Signature Plus Microcoagulation System (ITC, Piscataway, NJ, USA)” [ 13 ][ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a systemic response of the entire body to high altitude is triggered by hypoxia (7,8). Hypoxia is an integral part of the pathophysiology of many diseases, including chronic obstructive pulmonary disease (9), heart failure (10,11), sleep apnea syndrome (12), anemia (13), and cancer, and its basic research can reveal mechanisms that may 1 day be exploited in therapy development (14).…”
Section: Introductionmentioning
confidence: 99%